Peran dan Strategi Guru dalam Pendidikan Nilai untuk Generasi Alpha - Ahmad Arif; Cici Syaidatun Amalya; Rahmadani Indah Nasution; Amin Harahap (Pancasila and Civics Education Journal, 2026)
Abstract: The moral crisis among young people, especially Generation Alpha (born 2010–2024), is exacerbated by digital disruption, technological dependence, and low empathy. Teachers play a central role in value education but need adaptive strategies. This study uses a descriptive qualitative literature review, analyzing twelve relevant sources on teacher roles, strategies, and competencies in value education for Generation Alpha.  Generation Alpha has unique characteristics: digital natives, visual learners, critical thinkers, but vulnerable to digital addiction and low interpersonal empathy. Teachers perform three main roles: as educators (linking materials with values), as teachers (selecting appropriate learning models), and as trainers (providing direct examples). The most effective strategy is consistent teacher role modeling. The combination of transmission approaches (direct value inculcation through habituation) and construction approaches (value development through reflection, moral dilemmas) is essential. Required teacher competencies include pedagogical, professional, personality, and social competencies, shaped through formal education, non‑formal training, and teaching experience. Successful value education for Generation Alpha requires synergy among three pillars (family, school, community) and continuous teacher professional development. This study contributes an integrative model of teacher roles and strategies for character building in the digital era.Keywords: Value Education; Generation Alpha; Teacher Roles; Teacher Strategies; Character EducationAbstrak: Krisis moral di kalangan anak muda, khususnya Generasi Alpha (lahir 2010–2024), diperparah oleh disrupsi digital, ketergantungan teknologi, dan rendahnya empati. Guru memainkan peran sentral dalam pendidikan nilai tetapi membutuhkan strategi adaptif. Studi ini menggunakan tinjauan literatur kualitatif deskriptif, menganalisis dua belas sumber relevan tentang peran, strategi, dan kompetensi guru dalam pendidikan nilai untuk Generasi Alpha. Generasi Alpha memiliki karakteristik unik: penduduk asli digital, pembelajar visual, pemikir kritis, tetapi rentan terhadap kecanduan digital dan rendahnya empati interpersonal. Guru menjalankan tiga peran utama: sebagai pendidik (menghubungkan materi dengan nilai-nilai), sebagai pengajar (memilih model pembelajaran yang tepat), dan sebagai pelatih (memberikan contoh langsung). Strategi yang paling efektif adalah pemodelan peran guru yang konsisten. Kombinasi pendekatan transmisi (penanaman nilai langsung melalui pembiasaan) dan pendekatan konstruksi (pengembangan nilai melalui refleksi, dilema moral) sangat penting. Kompetensi guru yang dibutuhkan meliputi kompetensi pedagogis, profesional, kepribadian, dan sosial, yang dibentuk melalui pendidikan formal, pelatihan non-formal, dan pengalaman mengajar. Pendidikan nilai yang sukses untuk Generasi Alpha membutuhkan sinergi antara tiga pilar (keluarga, sekolah, masyarakat) dan pengembangan profesional guru yang berkelanjutan. Studi ini memberikan kontribusi berupa model integratif peran dan strategi guru untuk pembentukan karakter di era digital.Kata Kunci: Pendidikan Nilai; Generasi Alpha; Peran Guru; Strategi Guru; Pendidikan Karakter